The Relationship between the Social Environment and Discipline of Santri TPQ Surau Tabek Payolansek Payakumbuh City - Asiah, Siti; Setiawati, Setiawati (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2025)
This research was motivated by the low level of spiritual discipline at TPQ Surau Tabek Payolansek. This is thought to be caused by several factors, one of which is a less supportive social environment. This research aims to see a picture of the social environment, a picture of santri discipline, and to see the relationship between the social environment and santri discipline at TPQ Surau Tabek Payolansek. This research uses a quantitative approach with a correlational type of research. The population of this study was 31 students at TPQ Surau Tabek Payolansek, while the sample was 24 students. Samples were taken using the Stratified Random Sampling technique. Data collection techniques using questionnaires. The data analysis technique uses the percentage formula and the Spearman Rho formula to see the relationship between the two variables. The results of this research show that: 1) The description of the social environment at TPQ Surau Tabek Payolansek Payakumbuh City is categorized as poor. 2) The description of student discipline at TPQ Surau Tabek Payolansek Payakumbuh City is categorized as low. 3) There is a very significant relationship between the social environment and the discipline of students at TPQ Surau Tabek Payolansek Payakumbuh City.